The Poetics of Aqidah Education: Faith Purification in E. Abdullah's Tahlil Pupujian - Roni Nugraha Nugraha; Imas Karyamah (AL-IBANAH, 2026)
This article examines the poeticization of Islamic creed (aqidah) education through E. Abdullah's Tahlil poetry, which embodies the spirit of theological purification. The findings reveal that Abdullah's work represents a poetic form of creedal education employing metaphorical, satirical, and ironic language to deliver theological critiques against tahlilan rituals and the concept of merit transfer (iwadl al-thawab) - prazctices he argues lack strong foundations in the Quran and authentic hadith. From an educational perspective, Abdullah's Tahlil poetry serves as a medium for critical Islamic education. Through its aesthetic approach, the work not only conveys Islamic teachings but also provides reflective space to critically examine religious traditions often practiced without robust theological basis. The poeticization of tahlil functions as a creedal pedagogy, urging audiences to reorient toward authoritative sources: the Quran, authentic hadith, and recognized scholars. This approach transforms aqidah education beyond rote memorization and ritual practice, fostering critical consciousness among learners.